Biological response of osteoblasts to zirconia manufactured via FFF, DLP, and milling - Roser, Christoph; Erber, Ralf; Zenthöfer, Andreas; Rues, Stefan; Lux, Christopher J.; Nötzel, Dorit; Eickhoff, Ralf; Hanemann, Thomas (Journal of Functional Biomaterials, 2025)
(1) Background: Zirconia (ZrO2) is increasingly used in dental implantology due to its biocompatibility and favorable mechanical and biological properties. While subtractive and stereolithographic additive manufacturing techniques are well established, the application of Fused Filament Fabrication (FFF) for zirconia-based dental implants remains largely unexplored. (2) Methods: Cylindrical ZrO2 specimens were fabricated using three different manufacturing techniques: milling (MIL), Digital Light Processing (DLP), and FFF. Surface topography was analyzed via white-light interferometry. Human fetal osteoblasts (hFOBs 1.19) were cultured on the specimens to evaluate cell adhesion after 4 and 24 h, proliferation for 4 days, cell surface coverage after 4 and 24 h, and osteogenic gene expression (RUNX2, ALPL, and BGLAP) after 24 h, 48 h, 7 days, and 14 days. (3) Results: The FFF samples exhibited significantly higher surface roughness than the MIL and DLP specimens. After 24 h, enhanced cell adhesion and the highest proliferation rates were observed on FFF surfaces. At 14 days, gene expression analysis revealed elevated expression of BGLAP on FFF surfaces, suggesting advanced osteogenic differentiation compared to MIL and DLP. (4) Conclusions: The inherent surface roughness of FFF-printed zirconia appears to promote osteogenic activity without additional surface treatment. These findings suggest that FFF may constitute a viable manufacturing method for the fabrication of customized zirconia components in dental implantology, warranting further investigations, particularly regarding their mechanical performance.
Veröffentlicht: 23. Oktober 2025
Gesehen am 26.01.2026